THIADIAZOLE ANALOGS AS POTENTIAL PHARMACOLOGICAL AGENTS: A BRIEF REVIEW - Kaur, Gagandeep; Singh, Randhir (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
<!– [if gte mso 9]> <![endif]–> Recently, heterocyclic compounds analogues and their derivatives have attracted strong interest in medicinal chemistry due to their biological and pharmacological properties. The small and simple thiadiazole nucleus possesses numerous biological properties like - antitumor, antimicrobial, anti-inflammatory, anticonvulsant, and antidiabetic activities. These activities are also possessed by its substituted derivatives as well. The present review focuses on pharmacological activities of thiadiazole derivatives <!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>